Eren Yeager’s Free Will in the Perspective of John Calvin - Dethan, Stanley (Moriah Theological Seminary, 2024)
This study examines the theme of free will in the character of Eren Yeager from Attack on Titan through the lens of John Calvin’s theological framework, particularly his doctrines on human nature, predestination, and the limits of human autonomy as articulated in Institutes of the Christian Religion and selected sermons. Employing a qualitative literature review, the research integrates theological analysis with cultural interpretation, drawing on both Calvinist texts and contemporary scholarship on the intersection of theology and popular culture. Key narrative moments in Eren’s arc, especially his obsession with freedom, the inevitability of his actions, and his ultimate self-sacrifice are interpreted in light of Calvin’s understanding of divine sovereignty and compatibilism. It is important to note that this study does not intend to serve as a doctrinal defense or theological “proof-text” for Calvinism. Rather, the analysis seeks to explore how a popular fictional narrative can function as a lens for reflecting on longstanding theological debates about destiny, moral responsibility, and the human condition. By engaging with Eren’s struggle as a “slave to freedom” and his inability to alter a predetermined future, the article invites readers to consider the enduring relevance of theological concepts in contemporary cultural storytelling.